PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW MATERI ENERGI DAN PERUBAHANNYA PADA PESERTA DIDIK DI KELAS III SDN BANJAREJO - Devi Indri Febriyana; Ismail Marzuki (Universitas Muhammadiyah Gresik, 2020)
Application of the Jigsaw Type Cooperative Model Material Energy and Changes for Students in Class III of Banjarejo Elementary School (Guided by Mr. Dr. Irwani Zawawi and Mr.Ismail Marzuki. M.Pd).The purpose of this study was to find out how the application of the jigsaw type cooperative model material energy and changes for students in class III of Banjarejo Elementary School.This research uses field research, so that it can be called the type of qualitative research. Qualitative research is research that produces descriptive data.The students in class III of Banjaarejo Elementary during the learning process of Natural Sciences, students tend to be passive and more active teachers. Students listen more often to what the teacher explains and only accept what is explained by the teacher. This study aims to apply the jigsaw type cooperative learning model material energy and changes for students in class III of Elementary School. Then a qualitative descriptive study was conducted, also observed teacher activity, student activity and student learning outcomes. The results of this study indicate that teacher activity in meetings 1 and 2 had the first meeting score of 76.19% and for the second meeting, 92.85%, by achieving very good criteria, student activity scores 83.3% with very good criteria, and the results of tests of understanding concepts related to material energy and changes shows that the value of students gets 83.7%..